Surgical management of dentigerous cyst and keratocystic odontogenic tumor in children: a conservative approach and 7-year follow-up - Maria Cristina Zindel Deboni; Mariana Aparecida Brozoski; Andreia Aparecida Traina; Renata Rodrigues Acay; Maria da Graça Naclério-Homem (Journal of Applied Oral Science, 2012)
Dentigerous cyst (DC) is one of the most common odontogenic cysts of the jaws and rarely recurs. On the other hand, keratocystic odontogenic tumor (KCOT), formerly known as odontogenic keratocyst (OKC), is considered a benign unicystic or multicystic intraosseous neoplasm and one of the most aggressive odontogenic lesions presenting relatively high recurrence rate and a tendency to invade adjacent tissue. Two cases of these odontogenic lesions occurring in children are presented. They were very similar in clinical and radiographic characteristics, and both were treated by marsupialization. The treatment was chosen in order to preserve the associated permanent teeth with complementary orthodontic treatment to direct eruption of the associated permanent teeth. At 7-years of follow-up, none of the cases showed recurrence.